Membumikan Pancasila di Dunia Kesehatan: Hambatan dan Tantangannya - Afanindya Bias Maharani; Andrias Safa Ramadhani; Humaira Shahnaz; Khuladista Nafla Favela; Nabila Windy Alfarizy; Qorina Aiman Wachdin; Sholikul Hadi (Universitas 45 Surabaya, 2024)
Public awareness in the application of the five principles of Pancasila has not been optimally implemented in Indonesian society, especially in the world of health. This study was motivated by health service officers who are at the forefront in providing health services to patients. The purpose of this study was to determine the implementation, obstacles, challenges in grounding Pancasila and how to solve it in the world of health. This study uses a qualitative descriptive approach, through observation and analyzing various data sources from existing research. The results of the study indicate that the world of health in Indonesia faces very serious challenges, especially in realizing Pancasila character education in the health sector because the ability of health workers is not evenly distributed and there are limited facilities and infrastructure in health facilities. However, they are still required to be able to implement the application of good, superior, innovative, and Pancasila-based traits. Health providers and medical personnel must be responsive in following up on these provisions and the government must also provide incentives and special facilities and increase funds to support facilities and infrastructure in the world of health so that they can produce superior resources with Pancasila personalities.